Connections of the dorsomedial hypothalamic nucleus from the forebrain structures in the rat - ONAT, FİLİZ; GÜLHAN, REZZAN; ŞEHİRLİ, ÜMİT SÜLEYMAN (KARGER, 2002)
The dorsomedial hypothalamic nucleus (DMH) has been implicated as an area controlling autonomic activity. The aim of this study was to demonstrate connections of the anterior and posterior DMH to the forebrain structures, using a horseradish peroxidase (HRP) retrograde axonal transport technique in rats. The results of HRP labelling show that the anterior and posterior DMH indicate a number of differences in their connections. The posterior DMH has intense connections with the cortex (cingulate, frontal, parietal and insular), amygdala (lateral and basolateral) and hippocampus (CA1 and CA2), whereas the anterior DMH has faint connections with the cortex (cingulate, frontal and parietal) and prominent connections with the septal and bed nucleus of stria terminalis. These differences in connections of the DMH may provide sites for the specific autonomic function integrated by the DMH. Copyright (C) 2002 S. Karger AG, Basel.
Keywords: dorsomedial hypothalamic nucleus; horseradish peroxidase; rat; CARDIOVASCULAR-RESPONSES; PARAVENTRICULAR NUCLEUS; INSULAR CORTEX; INVOLVEMENT; PATHWAYS; REGION